Synthesis and fluorescent properties of N(9)-alkylated 2-amino-6-triazolylpurines and 7-deazapurines - Šišuļins, Andrejs; Bucevičius, Jonas; Tseng, Yu-Ting; Novosjolova, Irina; Traskovskis, Kaspars; Bizdēna, Ērika; Chang, Huan-Tsung; Tumkevičius, Sigitas; Turks, Māris (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of novel fluorescent N(9)-alkylated 2-amino-6-triazolylpurine and 7-deazapurine derivatives is described. A new C(2)-regioselectivity in the nucleophilic aromatic substitution reactions of 9-alkylated-2,6-diazidopurines and 7-deazapurines with secondary amines has been disclosed. The obtained intermediates, 9-alkylated-2-amino-6-azido-(7-deaza)purines, were transformed into the title compounds by CuAAC reaction. The designed compounds belong to the push–pull systems and possess promising fluorescence properties with quantum yields in the range from 28% to 60% in acetonitrile solution. Due to electron-withdrawing properties of purine and 7-deazapurine heterocycles, which were additionally extended by triazole moieties, the compounds with electron-donating groups showed intramolecular charge transfer character (ICT/TICT) of the excited states which was proved by solvatochromic dynamics and supported by DFT calculations. In the 7-deazapurine series this led to increased fluorescence quantum yield (74%) in THF solution. The compounds exhibit low cytotoxicity and as such are useful for the cell labelling studies in the future.
Keywords: 7-deazapurines; fluorescence; nucleophilic aromatic substitution; purines; push–pull systems; pyrrolo[2,3-d]pyrimidines

(untitled) - Skalski, B.; Steer, R. P.; Verrall, R. E. (J. Am. Chem. Soc., 1991)

(untitled) - Legraverend, M. (Tetrahedron, 2008)

(untitled) - Wierzchowski, J. (Curr. Top. Biophys., 2010)

(untitled) - Manvar, A.; Shah, A. (Tetrahedron, 2013)

(untitled) - Matarazzo, A.; Hudson, R. H. E. (Tetrahedron, 2015)

(untitled) - Sharma, S.; Singh, J.; Ojha, R.; Singh, H.; Kaur, M.; Bedi, P. M. S.; Nepali, K. (Eur. J. Med. Chem., 2016)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Eur. J. Org. Chem., 2015)

(untitled) - Perlíková, P.; Hocek, M. (Med. Res. Rev., 2017)

(untitled) - De Coen, L. M.; Heugebaert, T. S. A.; García, D.; Stevens, C. V. (Chem. Rev., 2016)

(untitled) - Tumkevicius, S.; Dodonova, J. (Chem. Heterocycl. Compd., 2012)

(untitled) - De Ornellas, S.; Slattery, J. M.; Edkins, R. M.; Beeby, A.; Baumann, C. G.; Fairlamb, I. J. S. (Org. Biomol. Chem., 2015)

(untitled) - Butler, R. S.; Myers, A. K.; Bellarmine, P.; Abboud, K. A.; Castellano, R. K. (J. Mater. Chem., 2007)

(untitled) - Vabre, R.; Legraverend, M.; Piguel, S. (Dyes Pigm., 2014)

(untitled) - Saito, Y.; Suzuki, A.; Imai, K.; Nemoto, N.; Saito, I. (Tetrahedron Lett., 2010)

(untitled) - Seela, F.; Schweinberger, E.; Xu, K.; Sirivolu, V. R.; Rosemeyer, H.; Becker, E.-M. (Tetrahedron, 2007)

(untitled) - Hudson, R. H. E.; Dambenieks, A. K.; Viirre, R. D. (Synlett, 2004)

(untitled) - Sinkeldam, R. W.; Greco, N. J.; Tor, Y. (Chem. Rev., 2010)

(untitled) - Dyrager, C.; Börjesson, K.; Dinér, P.; Elf, A.; Albinsson, B.; Wilhelmsson, L. M.; Grøtli, M. (Eur. J. Org. Chem., 2009)

(untitled) - Greco, N. J.; Tor, Y. (Tetrahedron, 2007)

(untitled) - Gaied, N. B.; Glasser, N.; Ramalanjaona, N.; Beltz, H.; Wolff, P.; Marquet, R.; Burger, A.; Mély, Y. (Nucleic Acids Res., 2005)

(untitled) - Zilbershtein-Shklanovsky, L.; Weitman, M.; Major, D. T.; Fischer, B. (J. Org. Chem., 2013)

(untitled) - Rankin, K. M.; Sproviero, M.; Rankin, K.; Sharma, P.; Wetmore, S. D.; Manderville, R. A. (J. Org. Chem., 2012)

(untitled) - Mitsui, T.; Kimoto, M.; Kawai, R.; Yokoyama, S.; Hirao, I. (Tetrahedron, 2007)

(untitled) - Zayas, J.; Annoual, M.; Das, J. K.; Felty, Q.; Gonzalez, W. G.; Miksovska, J.; Sharifai, N.; Chiba, A.; Wnuk, S. F. (Bioconjugate Chem., 2015)

(untitled) - Kovaļovs, A.; Novosjolova, I.; Bizdēna, Ē.; Bižāne, I.; Skardziute, L.; Kazlauskas, K.; Jursenas, S.; Turks, M. (Tetrahedron Lett., 2013)

(untitled) - Kavoosi, S.; Rayala, R.; Walsh, B.; Barrios, M.; Gonzalez, W. G.; Miksovska, J.; Mathivathanan, L.; Raptis, R. G.; Wnuk, S. F. (Tetrahedron Lett., 2016)

(untitled) - Tokugawa, M.; Kaneko, K.; Saito, M.; Kanamori, T.; Masaki, Y.; Ohkubo, A.; Sekine, M.; Seio, K. (Chem. Lett., 2015)

(untitled) - Sabat, N.; Nauš, P.; Matyašovský, J.; Dziuba, D.; Slavětínská, L. P.; Hocek, M. (Synthesis, 2016)

(untitled) - Bucevicius, J.; Skardziute, L.; Dodonova, J.; Kazlauskas, K.; Bagdziunas, G.; Jursenas, S.; Tumkevicius, S. (RSC Adv., 2015)

(untitled) - Neef, A. B.; Samain, F.; Luedtke, N. W. (ChemBioChem, 2012)

(untitled) - Venkatesh, V.; Shukla, A.; Sivakumar, S.; Verma, S. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Li, J.; Zhang, Y.; Zhang, H.; Xuan, X.; Xie, M.; Xia, S.; Qu, G.; Guo, H. (Anal. Chem. (Washington, DC, U. S.), 2016)

(untitled) - Li, J.-P.; Wang, H.-X.; Wang, H.-X.; Xie, M.-S.; Qu, G.-R.; Niu, H.-Y.; Guo, H.-M. (Eur. J. Org. Chem., 2014)

(untitled) - Saito, Y.; Suzuki, A.; Ishioroshi, S.; Saito, I. (Tetrahedron Lett., 2011)

(untitled) - Pratibha; Singh, S.; Sivakumar, S.; Verma, S. (Eur. J. Inorg. Chem., 2017)

(untitled) - Butler, R. S.; Cohn, P.; Tenzel, P.; Abboud, K. A.; Castellano, R. K. (J. Am. Chem. Soc., 2009)

(untitled) - Yang, Y.; Cohn, P.; Eom, S.-H.; Abboud, K. A.; Castellano, R. K.; Xue, J. (J. Mater. Chem. C, 2013)

(untitled) - Yang, Y.; Cohn, P.; Dyer, A. L.; Eom, S.-H.; Reynolds, J. R.; Castellano, R. K.; Xue, J. (Chem. Mater., 2010)

(untitled) - Bucevicius, J.; Turks, M.; Tumkevicius, S. (Synlett, 2018)

(untitled) - Cīrule, D.; Ozols, K.; Platnieks, O.; Bizdēna, Ē.; Māliņa, I.; Turks, M. (Tetrahedron, 2016)

(untitled) - Ozols, K.; Cīrule, D.; Novosjolova, I.; Stepanovs, D.; Liepinsh, E.; Bizdēna, Ē.; Turks, M. (Tetrahedron Lett., 2016)

(untitled) - Lu, W.; Sengupta, S.; Petersen, J. L.; Akhmedov, N. G.; Shi, X. (J. Org. Chem., 2007)

(untitled) - Zatloukal, M.; Jorda, R.; Gucký, T.; Řezníčková, E.; Voller, J.; Pospíšil, T.; Malínková, V.; Adamcová, H.; Kryštof, V.; Strnad, M. (Eur. J. Med. Chem., 2013)

(untitled) - Gucký, T.; Jorda, R.; Zatloukal, M.; Bazgier, V.; Berka, K.; Řezníčková, E.; Béres, T.; Strnad, M.; Kryštof, V. (J. Med. Chem., 2013)

(untitled) - Morales, F.; Ramírez, A.; Conejo-García, A.; Morata, C.; Marchal, J. A.; Campos, J. M. (Eur. J. Med. Chem., 2014)

(untitled) - Calderón-Arancibia, J.; Espinosa-Bustos, C.; Cañete-Molina, Á.; Tapia, R. A.; Faúndez, M.; Torres, M. J.; Aguirre, A.; Paulino, M.; Salas, C. O. (Molecules, 2015)

(untitled) - Malínková, V.; Řezníčková, E.; Jorda, R.; Gucký, T.; Kryštof, V. (Bioorg. Med. Chem., 2017)

(untitled) - Komodziński, K.; Lepczyńska, J.; Gdaniec, Z.; Bartolotti, L.; Delley, B.; Franzen, S.; Skalski, B. (Photochem. Photobiol. Sci., 2014)

(untitled) - Pignatello, R.; Puleo, A.; Acquaviva, R.; Di Giacomo, C.; Vanella, A.; Puglisi, G. (J. Drug Delivery Sci. Technol., 2004)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Tetrahedron Lett., 2013)

(untitled) - Novosjolova, I.; Bizdēna, Ē.; Turks, M. (Phosphorus, Sulfur Silicon Relat. Elem., 2015)

(untitled) - Bucevičius, J.; Tumkevičius, S. (Chemija, 2015)

(untitled) - Williams, A. T. R.; Winfield, S. A.; Miller, J. N. (Analyst, 1983)

(untitled) - Reichardt, C. (Chem. Rev., 1994)

(untitled) - Grabowski, Z. R.; Rotkiewicz, K.; Rettig, W. (Chem. Rev., 2003)

(untitled) - Neef, A. B.; Luedtke, N. W. (ChemBioChem, 2014)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2009)